(untitled) (Annals of Medical Research, 2021)
Aim: To evaluate the results of retrograde intrarenal surgery (RIRS) in stones with anomaly in the kidney.Material and Methods: Between April 2016 and November 2018, the data of 350 patients undergoing retrograde intrarenal surgery due to kidney stones were retrospectively examined.Patients with stones in the kidney with anomalies were recorded. Demographic data, localization of the stone, size, and success and complication rates were reviewed.In the post-operative controls, stones that were 2 mm and below were accepted as stone-free.Postoperative success was evaluated as stone-free at the 1st and 3rd months.Results: The mean age of the patients was 50.9 ± 15.8 (20-78).RIRS was performed in 29 kidneys with anomalies.Ten patients had horseshoe kidneys, 2 patients had ectopic pelvic kidneys, 13 patients had double collecting system and 4 patients had rotation anomalies.The mean stone size was 16.3 ± 6.1 (8-30) mm. The postoperative 1st and 3rd month stone-free rate was 48.2% and 51.7%, respectively.The complication developed in 4 (13.7%) patients. All of these were minor complications.Second procedure was applied to 14 of the remaining patients. Conclusion: In the treatment of kidney stones with anomalies, RIRS is reliable with low complication rates, but the patient should be informed about the need for additional procedures due to low stone-free rates.